2016
DOI: 10.1007/jhep07(2016)085
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of an anisotropic N=4 super Yang-Mills plasma via holography

Abstract: Black hole solutions of type IIB supergravity were previously found that are dual to N=4 supersymmetric Yang-Mills plasma with an anisotropic spatial deformation. In the zero temperature limit, these black holes approach a Liftshitz like scaling solution in the IR. It was recently shown that these black holes are unstable, and at low temperatures there is a new class of black hole solutions that are thermodynamically preferred. We extend this analysis, by considering consistent truncations of the Kaluza-Klein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…In general this will not be the case 7 and the solution will also contain a significant admixture of a solution with outgoing boundary conditions imposed at z = z 1 . To proceed, for the scaling region z 1 < z < z 2 we assume 8) and also demand that the potential satisfies…”
Section: Spectral Weight Of Operators In the Rg Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general this will not be the case 7 and the solution will also contain a significant admixture of a solution with outgoing boundary conditions imposed at z = z 1 . To proceed, for the scaling region z 1 < z < z 2 we assume 8) and also demand that the potential satisfies…”
Section: Spectral Weight Of Operators In the Rg Flowsmentioning
confidence: 99%
“…The Q-lattice constructions of this paper used a very specific global symmetry of the maximally supersymmetric N = 8 gauged supergravity theory. The 70 scalars of this theory parametrise the coset E 7(7) /SU (8) and we utilised a specific truncation that kept scalars parametrising two SL(2)/SO(2) factors in E 7(7) /SU (8). Furthermore, we exploited the fact that the scalar potential was invariant under SO(2) 2 and this was utilised to construct our Q-lattice ansatz.…”
Section: Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the particular case of X 5 = S 5 , associated with N = 4 Yang-Mills theory, it is known that the Lifshitz-like solution is unstable [12]. At finite temperature it was shown that the linear axion solutions have phase transitions [15,16] leading to new branches of solutions. It would be interesting to investigate whether similar instabilities and phase transitions occur for the τ -lattices we have constructed here.…”
Section: Discussionmentioning
confidence: 99%
“…This in principle could lead to the observation of stars more compact than the ones allowed by isotropic matter, see, e.g., [3,4]. Strongly coupled anisotropic phases have been studied using holography in a variety of setups, including axionic/dilatonic sources [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], electric [21][22][23] and magnetic fields [24][25][26][27][28][29][30][31][32][33] or both [34][35][36][37][38], and p-wave superfluids [39][40][41][42][43][44]. Strongly coupled holographic matter has also been studied in the context of compact stars [45][46][47][48][49][...…”
Section: Introductionmentioning
confidence: 99%